The Use of Peanut Flour as A Substitute for Almond Flour in Making Macarons - Aprilya, Putu; Sunada, I Nyoman; Parbandari, Anak (Gastronomy Tourism Journal, 2021)
Macaron is a type of pastry that is popular in the community. The basic ingredient for making macarons cake is almond flour. Almond as a basic ingredient of flour, has a fairly expensive price, so macarons cake is categorized as an expensive pastry and has not been fully reached by the public. Another type of nut that can replace almonds is peanuts. Peanuts are easy to find in Indonesia and are spread in several provinces. The relatively cheap price of peanuts and high nutritional content can be an alternative to almond flour. The object of this study is the quality of the macarons using groundnut peanut flour. The stages of this study consist of experiments, documentation, and organoleptic tests or sensory tests. The results of this study indicate that the macarons cake made from peanut flour meets the indicators of a good macarons cake. Based on organoleptic test or test sensory, macaron peanut flour-based macarons starch peanuts have a crispy texture is very crisp, the colors are rather pale, macarons are made from peanuts have a surface that is smooth and there are no cracks, in addition pied (foot) on the peanut-based macarons are peanut-based already appear or have legs.